PENGAWETAN DUA JENIS KAYU IRIAN JAYA MEMAKAI BAHAN PENGAWET KOPPER FORMULA 7 SECARA RENDEMAN DINGIN - Sasa Abdurrohim; R Endahwati; S B Husodo (Jurnal Penelitian Hasil Hutan, 1991)
The penetration of wood preservative of ten wood species from Lampung was studied. The obaervation was conduct- ed afier the timber had  been preserved by diffusion method. The BFCA 30% and wood •mples  of 6 cm by 10 cm by 200 cm were used in this experiment.The  results showed that wood .species  haB  significant effect  on penetration,  whi'le duration of  di/fusion storage period haB  the mme  effect  only on keruing, damar a8Clm,  balam and cengal banglai.Eight weeks of storage was better than 4  weeks on those timber,.  but not for the other species. According to IUFRO clasBifieation,pulai. kayu tabu and bintangur can be clasBifiedas permeable, while the others were classified aB  moderate